2021
DOI: 10.1097/hnp.0000000000000477
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Reiki on Pain, Fatigue, and Quality of Life in Adolescents With Dysmenorrhea

Abstract: This randomized, single-blind, placebo-controlled study was conducted to evaluate the effect of Reiki applications on pain, fatigue, and quality of life in adolescents with dysmenorrhea. There were 38 patients in the Reiki group and 37 in the placebo-controlled group. Reiki was found to be effective on pain and fatigue in adolescents with dysmenorrhea but with no effect on the quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Reiki to be effective in the management of multiple symptoms. 8,9,14 These effects support a reduction in symptoms and an increase in the quality of life of patients. The purpose of this study was to investigate the effects of Reiki on fatigue and anxiety levels in hemodialysis patients.…”
mentioning
confidence: 66%
See 4 more Smart Citations
“…Reiki to be effective in the management of multiple symptoms. 8,9,14 These effects support a reduction in symptoms and an increase in the quality of life of patients. The purpose of this study was to investigate the effects of Reiki on fatigue and anxiety levels in hemodialysis patients.…”
mentioning
confidence: 66%
“…It was determined in a study conducted with adolescents with dysmenorrhea that the Reiki intervention resulted in a decrease in general fatigue levels. 9 A different study wherein fatigue was studied also reported that Reiki application was effective in lowering fatigue levels. 22 Other studies with different samples have also revealed that Reiki reduces fatigue levels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations